2010
DOI: 10.1016/j.neuroimage.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Neural processing of asynchronous audiovisual speech perception

Abstract: The temporal synchrony of auditory and visual signals is known to affect the perception of an external event, yet it is unclear what neural mechanisms underlie the influence of temporal synchrony on perception. Using parametrically varied levels of stimulus asynchrony in combinations with BOLD fMRI, we identified two anatomically distinct subregions of multisensory superior temporal cortex (mSTC) that showed qualitatively distinct BOLD activation patterns. A synchrony-defined subregion of mSTC (synchronous > a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 53 publications
7
151
1
Order By: Relevance
“…Two main findings arose from this study. The first one was related to the superior temporal sulcus (STS), an area classically related to multisensory integration in and outside the speech domain (Beauchamp et al, 2004a;Calvert et al, 2000;Fairhall and Macaluso, 2009;Miller and D'Esposito, 2005;Nath and Beauchamp, 2012;Noesselt et al, 2012;Beauchamp et al, 2004aBeauchamp et al, , 2012Stevenson et al, 2010;Stevenson et al, 2011;Stevenson and James, 2009). This study showed a higher BOLD response in the STS when participants focused their visual spatial attention on the lips that were congruent with the auditory stream than when they focused their attention toward the location of the incongruent lips.…”
Section: Neuroimaging Studies Measuring Attentional Effects On Av Spementioning
confidence: 73%
See 2 more Smart Citations
“…Two main findings arose from this study. The first one was related to the superior temporal sulcus (STS), an area classically related to multisensory integration in and outside the speech domain (Beauchamp et al, 2004a;Calvert et al, 2000;Fairhall and Macaluso, 2009;Miller and D'Esposito, 2005;Nath and Beauchamp, 2012;Noesselt et al, 2012;Beauchamp et al, 2004aBeauchamp et al, , 2012Stevenson et al, 2010;Stevenson et al, 2011;Stevenson and James, 2009). This study showed a higher BOLD response in the STS when participants focused their visual spatial attention on the lips that were congruent with the auditory stream than when they focused their attention toward the location of the incongruent lips.…”
Section: Neuroimaging Studies Measuring Attentional Effects On Av Spementioning
confidence: 73%
“…The STS has been often highlighted as one of the main loci for MSI, especially but not exclusively, regarding AV integration of speech (Beauchamp et al, 2004a(Beauchamp et al, , 2004bCalvert et al, 2000;Fairhall and Macaluso, 2009;Miller and D'Esposito, 2005;Nath and Beauchamp, 2012;Noesselt et al, 2007;Noesselt et al, 2012;Stevenson et al, 2010Stevenson et al, , 2011Stevenson and James, 2009). In particular, two different parts of the STS have been found to activate depending on the nature of the audiovisual manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted though that even during congruent speech auditory and visual signals are not necessarily temporally synchronous (Schwartz & Savariaux, 2014;Chandrasekaran, Trubanova, Stillittano, Caplier, & Ghazanfar, 2009), and speech signals are still perceived as congruent if the temporal asynchrony does not exceed a certain maximum ( Van Wassenhove, Grant, & Poeppel, 2007). The STC is generally susceptible to these temporal differences between congruent and incongruent speech (Stevenson, Altieri, Kim, Pisoni, & James, 2010). …”
Section: Different Shades Of Audiovisual Congruencymentioning
confidence: 99%
“…Possible brain regions involved in the reweighting mechanism include networks that quantify temporal synchrony and perceptual binding of AV percepts. These regions span the primary cortices as well as the STC and regions along the temporal-parietal-occipital junction (Beauchamp et al 2004a(Beauchamp et al , 2004bBushara et al 2001;Calvert et al 2000;Liebenthal et al 2005;Macaluso et al 2004;Powers et al 2009;Stevenson et al 2010Stevenson et al , 2011. The classical view posits that this occurs via a central integrator, the pSTS-G (Beauchamp et al 2004a(Beauchamp et al , 2004bCalvert and Campbell 2003;Keil et al 2011;Miller and Fig.…”
Section: Reweighting Model Of Av Integrationmentioning
confidence: 99%